Newton Binomial Formulas in Schubert Calculus - Cordovez, Jorge; Gatto, Letterio; Santiago, Taíse (Revista Matemática Complutense, 2009)
We prove Newton's binomial formulas for Schub ert Calculus to determine num b ers of base p oint free linear series on the pro jective line with prescrib ed rami fication divisor supp orted at given distinct p oints.